Efficacy of combined strategies of physical activity, diet and sleep disorders as treatment in patients with chronic shoulder pain. A systematic review - Hamed Hamed, Dina; Struyf, Filip; Pruimboom, Leo; Navarro-Ledesma, Santiago (Frontiers in Physiology, 2023)
The objective of this systematic review was to analyze the existing scientific evidence on the influence of dietary strategies, exercise, and sleep disorders on the symptomatology of patients with chronic shoulder pain, as well as to assess the methodological quality of the literature collected. The selection criteria were as follows: we included randomized controlled clinical trials written in English that investigated the effects of such interventions in patients with chronic shoulder pain and excluded studies where pre-operative rehabilitation or rehabilitation combined with corticosteroid injections was performed. We searched six databases Pubmed, Cochrane Library, Web of Science, CINAHL, Sportdiscus and Scopus, using the keywords "shoulder pain", "fasting", "physical therapy modalities", "rehabilitation", "exercise", "circadian clocks" and "chronic pain" to select randomized controlled clinical trials conducted in humans and written in English. The last search was conducted on 24/01/2023. We used the tool proposed by the Cochrane Handbook to assess the risk of bias in the included studies. Of the 17 studies included, nine had a high risk of bias, two studies had an unclear risk of bias, and the remaining six studies had a low risk of bias. A total of 17 articles were selected, including ten studies that showed a positive influences of exercise on chronic shoulder pain and five studies that showed a negative influence of sleep disorders on this patient profile. The remaining two articles analyzed the influence of nutritional strategies and metabolic problems in patients with chronic shoulder pain. The total sample size of the 17 included articles amounted to 9,991 individuals. Studies confirm that exercise generates a hypoalgesic effect that improves chronic shoulder pain, functionality, and quality of life. Although dietary strategies and sleep disorders are known to influence chronic shoulder pain, there is a lack of studies that conduct interventions on these problems to assess how chronic shoulder pain varies. (PROSPERO:CRD42023379925).